Current trends in Oxygen enriched combustion : Application and scrutiny - Raguman. A, Abdul; D, Madhankumar; B, Ajith; V, Mohanasundaram; V, Nandhakumar (International Journal of Engineering and Technology, 2018)
The populace in the global scenario has drastically increased in the past decades. Due to this situation, the necessity of transportation also escalated which simultaneously raised the pollution levels. Nowadays the populace commonly prefers their individual vehicles rather than public transport system. This made the automotive manufacturers to come up with new technologies and to compensate the stringent norms introduced by several countries. Internal Combustion engine has been serving the world more than a century and plays a vital role in the means of transportation. Many types of research were made to enhance the efficiency of IC engines by the use of alternative fuels, alteration of the intake parameters, stroke variation, usage of alternative materials etc., At present scenario of IC engine, the efficiency ranges between 35 – 50 % based on the technology used. If more efficient IC engines are used it would meet the demand of depleting fossil fuels. Such engines may prevent the demise of fossil fuels. Thus our project deals with the prospect to discuss the phenomenal changes and effects occurring on IC engine when the working fluid is enriched oxygen.